2013
DOI: 10.5539/ijc.v5n2p12
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Structure, Thermal Stability, XR-Diffraction, and Infrared Study of Hexadecyltrimethylammonium Bromide–Modified Smectite

Abstract: We characterized the interlayer structure and morphology of modified natural clays. Organoclay-based materials are increasingly used for multiple applications. We modified a purified Na-bentonite using cation exchange with hexadecyltrimethyl ammonium bromide (HDTMA) and characterized it using; UV spectroscopy, X-ray diffraction, photoacoustic FTIR spectroscopy (PA-FTIR), thermogravimetric analysis (TGA) techniques, laser scattering distribution (LSD), atomic force microscopy (AFM) and transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Without going into too many details about each of these methods, it is clear to mention that they can provide useful information about the organization and aggregation of clay platelets and by a topographic visualization the changes resulting from the modification process. For example, TEM can be used to estimate the edge-surface areas of organoclays or for the characterization of the microstructure and morphology of pure organoclays [97]; in addition, the particle size and particle size distribution can easily be extracted from the AFM data [98,99]. TEM and SEM micrographs are usually exploited to characterize the layer stacking and the surfactant packing density of organoclays of classes that are most prepared in the literature [100][101][102].…”
Section: Microscopic Methodsmentioning
confidence: 99%
“…Without going into too many details about each of these methods, it is clear to mention that they can provide useful information about the organization and aggregation of clay platelets and by a topographic visualization the changes resulting from the modification process. For example, TEM can be used to estimate the edge-surface areas of organoclays or for the characterization of the microstructure and morphology of pure organoclays [97]; in addition, the particle size and particle size distribution can easily be extracted from the AFM data [98,99]. TEM and SEM micrographs are usually exploited to characterize the layer stacking and the surfactant packing density of organoclays of classes that are most prepared in the literature [100][101][102].…”
Section: Microscopic Methodsmentioning
confidence: 99%
“…All surfactants and salt were used with no further purification or modification of their properties. Surfactants selected for the present study are commercial surfactants with good thermal stability as reported in the literature. , Deionized water was used for preparation of surfactant solutions throughout the experiment. The surfactants used in this study are tabulated in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we investigated thermal degradation of sorption products to elucidate the mechanism of interaction between the surfactant and the bentonite matrix. There is relatively little research concerning thermal analysis of HDTMA-bentonite [10][11][12][13][14][15][16][17]; however, this problem has received sufficient scrutiny in the works concerning the analog of bentonite, montmorillonite [18][19][20][21][22]. The introduction of phosphate ions to a sorption system is a new problem, and there is a dearth of research concerning thermal analysis of HDTMA-P(V)-bentonite and its modifications with U(VI).…”
Section: Introductionmentioning
confidence: 99%